2014
DOI: 10.1371/journal.pone.0110242
|View full text |Cite
|
Sign up to set email alerts
|

The Coexistence of Antiphospholipid Syndrome and Systemic Lupus Erythematosus in Colombians

Abstract: ObjectivesTo examine the prevalence and associated factors related to the coexistence of antiphospholipid syndrome (APS) and systemic lupus erythematosus (SLE) in a cohort of Colombian patients with SLE, and to discuss the coexistence of APS with other autoimmune diseases (ADs).MethodA total of 376 patients with SLE were assessed for the presence of the following: 1) confirmed APS; 2) positivity for antiphospholipid (aPL) antibodies without a prior thromboembolic nor obstetric event; and 3) SLE patients withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 79 publications
(58 reference statements)
1
33
1
Order By: Relevance
“…Differences in the prevalence of APS associated with SLE by race have been reported (Table ), ranging from 2.9% in Iban patients from East Malaysia to 27.8% in Indian patients . We found a prevalence of APS in Caucasians (13.3%) similar to that reported in a prospective study that showed that 13.8% of Spanish SLE patients had concurrent APS, while we detected a lower prevalence of APS in Roma patients (28.8%) compared to that previously published (36%) .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Differences in the prevalence of APS associated with SLE by race have been reported (Table ), ranging from 2.9% in Iban patients from East Malaysia to 27.8% in Indian patients . We found a prevalence of APS in Caucasians (13.3%) similar to that reported in a prospective study that showed that 13.8% of Spanish SLE patients had concurrent APS, while we detected a lower prevalence of APS in Roma patients (28.8%) compared to that previously published (36%) .…”
Section: Discussionsupporting
confidence: 85%
“…90%, P = 0.03). Prevalence of APS associated with lupus varies according to race (Table ). It has been reported that APS prevalence in Chinese SLE patients is lower than in the Caucasian population .…”
Section: Introductionmentioning
confidence: 99%
“…Besides identifying antigens, others have identified potentially important antibodies. Antiphospholipid (aPL) antibodies are associated with some autoimmune diseases (24). Duftner et al (17) showed that peripheral aPL antibodies in AAA patients were associated with disease progression.…”
Section: Putative Autoantigens In Aaa Tissuementioning
confidence: 99%
“…Specifically, EGFR which interacts with SH2B3 associated with APS ( Supplementary Figure 2 ), is related to systemic lupus erythematosus (SLE) (88). Surprisingly, an increasing number of studies (8991) have found APS in patients with SLE. Also, SKAP2 bridge protein, which interacts with PTPN22 associated with ITP ( Supplementary Figure 2 ), is related to Crohn disease (92).…”
Section: Discussionmentioning
confidence: 99%